Analysis of Decorrelation Transform Gain for Uncoded Wireless Image and Video Communication - Ruiqin Xiong (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2016)
An uncoded transmission scheme called SoftCast has recently shown great potential for wireless video transmission. Unlike conventional approaches, SoftCast processes input images only by a series of transformations and modulates the coefficients directly to a dense constellation for transmission. The transmission is uncoded and lossy in nature, with its noise level commensurate with the channel condition. This paper presents a theoretical analysis for an uncoded visual communication, focusing on developing a quantitative measurements for the efficiency of decorrelation transform in a generalized uncoded transmission framework. Our analysis reveals that the energy distribution among signal elements is critical for the efficiency of uncoded transmission. A decorrelation transform can potentially bring a significant performance gain by boosting the energy diversity in signal representation. Numerical results on Markov random process and real image and video signals are reported to evaluate the performance gain of using different transforms in uncoded transmission. The analysis presented in this paper is verified by simulated SoftCast transmissions. This provide guidelines for designing efficient uncoded video transmission schemes